(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The critical concept of nursing shared governance is shared decision making between the bedside nurses and nurse leaders, which include areas such as resources, nursing research, evidence-based practice projects, new equipment purchases, and staffing. Aim: of this study was to examine the impact of shared governance training program on nurse managers` awareness and organizational commitment. Design: A quasi experimental research was utilized. Setting: The study was carried out at the New Kasr El Aini Teaching Hospital, which is affiliated to Cairo University. Subjects: A convenience sample of all nurse managers' at the selected hospital (n=45). Tools: Three tools were used for data collection; Index of Professional Nursing Governance Questionnaire (IPNG), Shared governance awareness tool and Organizational commitment questionnaire. Results: There was traditional professional nursing governance among the studied nurse managers (x̅±SD= 44.42±16.93), there was highly statistical significant difference (χ2= 86.23, p=0.00) among the studied nurse managers regarding level of total shared governance awareness between the different time periods, there was statistical insignificant difference (f= 0.33, p=0.72) among the studied nurse managers regarding total organizational commitment between the different time periods. Conclusion: based on the results of the present study it can be concluded that there was no statistically significance relation between shared governance and organizational commitment. Recommendations: it is a priority to apply the shared governance or adopting suitable governance model that focuses on strong leadership and a sound shared governance infrastructure; for allowing a professional practice environment.